Battling on the Home Front: Posttraumatic Stress Disorder and Conflict Behavior among Military Couples - Knobloch-Fedders, Lynne M. (Behav Ther, 2016)
This study evaluated interpersonal behavior differences among male military service members with and without PTSD and their female partners. Couples (N = 64) completed a 17-minute videotaped conflict discussion, and their interaction behavior was coded using the circumplex-based Structural Analysis of Social Behavior model (SASB; Benjamin, 1979; 1987; 2000). Within couples, the behavior of partners was very similar. Compared to military couples without PTSD, couples with PTSD displayed more interpersonal hostility and control. Couples with PTSD also exhibited more sulking, blaming, and controlling behavior, and less affirming and connecting behavior, than couples without PTSD. Results advance our understanding of the relational impacts of PTSD on military service members and their partners, and underscore the value of couple-based interventions for PTSD in the context of relationship distress.